PENGARUH PROGRAM KELUARGA HARAPAN TERHADAP PENINGKATAN KESEJAHTERAAN MASYARAKAT NANGA POTAI KECAMATAN SOKAN KABUPATEN MELAWI - Pelipa, Emilia Dewiwati; Clara, Bella Novita; Sore, Avelius Dominggus (STKIP Persada Khatulistiwa Sintang, 2023)
Social welfare is a condition where society's needs for a decent life are met, but the reality shows that there are still individuals who do not enjoy prosperity and are unable to live a decent life. This research aims to determine the effect of the family hope program on improving the welfare of the Nanga Potai community, Sokan District, Melawi Regency. This research uses quantitative research, the form of this research is simple regression analysis. The research population is all households receiving PKH benefits and the research sample of all PKH recipients in Nanga Potai village is 47 people. The location of this research is in Nanga Potai Village, Sokan District, Melawi Regency, West Kalimantan Province. Data collection techniques include questionnaires and documentation techniques. Data analysis was carried out quantitatively using inferential statistics. Testing instruments that include validity and reliability. Requirements testing uses the classic assumption test with hypothesis testing using the t test and KD test. The test results show that PKH has a positive effect on community welfare, meaning community welfare with the increasing presence of PKH in Nanga Potai village.